1986
DOI: 10.3171/jns.1986.64.6.0951
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacological analysis of the pathophysiological mechanisms of posttraumatic spinal cord ischemia

Abstract: A pharmacological analysis was carried out to determine the possible role of aberrant calcium fluxes, vasoactive arachidonic acid metabolites, and microvascular lipid peroxidation in the development of posttraumatic spinal cord white matter ischemia. Pentobarbital-anesthetized cats were treated intravenously 30 minutes before a 500-gm-cm contusion injury to the lumbar spinal cord with one of the following test drugs: the Ca++ channel antagonists verapamil, diltiazem, or nifedipine; the cyclo-oxygenase inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(95 citation statements)
references
References 50 publications
2
90
0
3
Order By: Relevance
“…Pretreatment with vitamin E has been shown to be protective in animal models of SCI. 2,53 Iwasa et al systemically studied the effects of vitamin E on injury of the spinal cord associated with ischemia in rats. 54,55 The results showed that the motor disturbance induced by SCI was greatly reduced and spinal cord blood flow was promptly restored and remained normal after injury in the vitamin E-supplemented group.…”
Section: Nucleusmentioning
confidence: 99%
“…Pretreatment with vitamin E has been shown to be protective in animal models of SCI. 2,53 Iwasa et al systemically studied the effects of vitamin E on injury of the spinal cord associated with ischemia in rats. 54,55 The results showed that the motor disturbance induced by SCI was greatly reduced and spinal cord blood flow was promptly restored and remained normal after injury in the vitamin E-supplemented group.…”
Section: Nucleusmentioning
confidence: 99%
“…On the other hand, high-dose oral vit E supplementation for 5 days before SCI acts to attenuate the progressive posttraumatic decrease in white matter spinal cord blood flow together with a significant enhancement in hind-limb motor function compared with non-vit E supplemented animals, this effect has been replicated in a rat compression SCI model. 29 In contrast, vit E deficiency has been shown to increase post-SCI LP and to attenuate motor functional recovery. 30 However, despite these effects, the value of vit E as an acute treatment for SCI is limited by the fact that it requires weeks to achieve a significant increase in parenchymal CNS tissue levels.…”
Section: Antioxidants In Sci Treatmentmentioning
confidence: 99%
“…The main cause was observed to be ischemia of the gray matter, a consequence of the intracellular entry of calcium, and edema of the perilesional white matter. 2,3 Experimentally, the photochemical model of a secondary lesion was described by Watson et al 4 in rats. The resultant photochemical reaction leads to vascular stasis and congestion, hemorrhagic necrosis of the central gray matter and edematous pale-staining white matter tracts.…”
Section: Objectif : Le Modèle Photochimique D'une Lésion Médullaire Rmentioning
confidence: 99%
“…Another important element of the cascade of events leading to cell ischemia is phospholipase activation in cell membranes. 3 Bupivacaine is an inhibitor of A2 phospholipase. 21 However, this inhibition was demonstrated in vitro with high doses of bupivacaine, larger than those used in clinical investigations and reaching cardiotoxic levels.…”
Section: Objectif : Le Modèle Photochimique D'une Lésion Médullaire Rmentioning
confidence: 99%
See 1 more Smart Citation